1954
DOI: 10.1111/j.1476-5381.1954.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

A Peripheral Action of Sodium Salicylate

Abstract: Sodium salicylate and related compounds are widely used for their antipyretic properties. It has been suggested that the antipyresis is due to an effect on the hypothalamus, leading to increased heat loss (Barbour, 1926;Guerra and Barbour, 1943). This concept, however, does not specify what effects salicylate would be expected to have on metabolic rate.The observation of Reid (1952), when studying the changes in acid-base balance, that sodium salicylate caused a marked increase in the 0°con-sumption of the rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
9
0

Year Published

1958
1958
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 3 publications
4
9
0
Order By: Relevance
“…Classic studies from the 1950s observed that salicylate stimulates mitochondrial uncoupling (53,59), and previous work established that mitochondrial Δψm is reduced by 1.0 mmol/L salicylate (54). Moreover, proton conductance is increased with 1.0 mmol/L salicylate treatment (present data and ref.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Classic studies from the 1950s observed that salicylate stimulates mitochondrial uncoupling (53,59), and previous work established that mitochondrial Δψm is reduced by 1.0 mmol/L salicylate (54). Moreover, proton conductance is increased with 1.0 mmol/L salicylate treatment (present data and ref.…”
Section: Discussionsupporting
confidence: 67%
“…This is the first study to suggest that salicylate-driven mitochondrial uncoupling is the primary mechanism of action to explain the host of beneficial effects associated with salicylate (11,49,50) and salsalate (6)(7)(8)14,51,52). Data from the present study and previous investigations suggest that mitochondrial uncoupling resulting from the protonophoric properties of salicylate explains the consistently observed increases in energy expenditure in murine models and human subjects treated with salicylate-based compounds (6,10,11,14,15,(52)(53)(54)(55)(56)(57)(58).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Decapitated or curarized dogs maintained in a total body respirator to keep ventilation constant showed the same increased oxygen consumption in response to salicylate administration as the intact animal (5). Furthermore, oxygen consumption has been shown to be increased in tissues removed from salicylatetreated animals (7) and in isolated tissue or mitochondrial preparations to which salicylates have been added (8,9). The increase in oxygen consumption is accompanied by a reduction in the esterification of inorganic phosphate, i.e., salicylates uncouple oxidative phosphorylation (7).…”
mentioning
confidence: 89%
“…Basal metabolic rate is increased in the intact animal (10)(11)(12), tissue oxygen consumption is stimulated in slices (13), and oxidative phosphorylation is uncoupled in isolated mitochondrial preparations (14,15). Indeed, several authors have commented on the similarity of 2,4-dinitrophenol and salicylate (6,8,16).…”
mentioning
confidence: 99%